Designing of Aplikasi Pendamping Diabetes (Si-PenDi) as a Control Tool for Type 2 Diabetes Mellitus Patients - Julaiha, Siti; Sembiring, Elma Viorentina; Pardilawati, Citra Yuliyanda (Jurnal Kesehatan, 2024)
Diabetes Mellitus is known as the mother of other diseases such as cardiovascular disease, kidney failure, and blindness. Indonesia ranks 5th in the world in terms of the number of Diabetes Mellitus sufferers in 2014. Non-compliance of patients with therapeutic recommendations can increase the risk of complications. Patient non-compliance is often caused by several factors, including forgetting to use medication, ADR, feeling healthy, and lack of education from health workers. The increasingly widespread use of Android-based applications among the public is an opportunity for patient consultations and reminding patients to be disciplined in using drugs so that they can improve patient clinical outcomes. Therefore, it is necessary to design an Aplikasi Pendamping Diabetes (Si-PenDi) as a control tool for type 2 diabetes mellitus patients undergoing therapy. This research aims to create the Aplikasi Pendamping Diabetes (Si-PenDi) as a tool to help control type 2 diabetes mellitus patients. The research is Research and Development research. The method is used to produce specific products and study the effectiveness of these products. This research reached TKT Level 2, making an Android-based technology application called the Si-PenDi (Diabetes Companion Application). The results obtained are that the Si-PenDi application has quite effective quality but cannot be said to be efficient and meet user satisfaction, so it is necessary to improve the design so that the application is better able to meet user expectations.